Measurement of Tissue Factor Activity in Whole Blood - Santucci, Richard A.; Erlich, Jonathan; Labriola, Joanne; Wilson, Mark; Kao, K. J.; Kickler, Thomas S.; Spillert, Charles; Mackman, Nigel (Thrombosis and Haemostasis, 2000)
High circulating levels of the procoagulant molecule tissue factor (TF) are associated with thrombosis in a variety of diseases including unstable angina, cancer, and sepsis. Currently, there are no clinical assays to measure the level of TF activity in whole blood. We present an assay called Tissue Factor Clotting Time (“TiFaCT™”) that detects fibrin formation in human blood. The mean baseline clotting time in a healthy population was 472 ± 94 s (mean ± SD, n = 150). Bacterial lipopolysaccharide (LPS or endotoxin) shortened the clotting time in a time-dependent manner. Inhibitory anti-TF antibodies prolonged the clotting time of LPS-stimulated blood, indicating that the shortened clotting time was due to induction of TF expression. Patients with unstable angina had shortened mean baseline clotting time (284 ± 86, n = 13) compared with healthy volunteers (474 ± 98, n = 30), suggesting that these patients had elevated levels of circulating TF. The TiFaCT assay should prove clinically useful in quantifying the levels of circulating TF in patients at risk of thrombosis.
Keywords: Tissue factor; whole blood; thrombosis